Pacfic environment outlook (UNEP NarobiKE, 2005)
Presents environmental trends by assimilating the drivers that directly and indirectly affect the state of the environment. Examines the linkages between social and economic activities and the environment in the Pacific SIDS, highlighting their social, economic and environmental vulnerability.
Keywords: ENVIRONMENT